Seasonal Variation of the Environmental Parameters along Fort Cochin Beach - K.V., Jayalakshmy; O., Raveendran; S., Sreeja (Fishery Technology, 2025)
Monthly observations on heterotrophic bacteria, organic carbon, temperature, salinity, dissolved oxygen, inorganic phosphate, nitrate, nitrite and ammonia from surface water and from water table level during high tide, mid tide and low tide were carried out in the Fort Cochin beach for a period of one year. Also, monthly observations on heterotrophic bacteria, organic carbon and temperature were carried out for the same period from sand during the three tidal levels at surface and water table level. The study showed that organic carbon in sand controlled the bacterial population to a great extent during high tide at surface and during low tide at water table level. Step-up multiple regression analysis showed that in water the interaction effect of inorganic phosphate and ammonia and that of ammonia and temperature were the most important parameters controlling the bacterial production whereas in the sand at the surface, temperature-organic carbon interaction effect was the controlling parameter. The results of the Q-mode analysis are also presented.